(untitled) (Journal of Plant Disease Sciences, 2018)
In-vitro evaluation of fungicides, bioagent and botanicals were undertaken against Rhizoctonia bataticola incitant of root rot of betelvine. Among fungicides carbendazim and combi product i.e. carboxin + thiram @ 0.1% restricted cent percent radial mycelial growth and persisted till seventh day while other test fungicides were not efficient to reduce the growth of Rhizoctonia bataticola. In the midst of antagonists, Trichoderma. harzianum was most effective in reducing the growth of pathogen to the extent of 46.81% while T. asperellum and Pseudomonas. fluorescens inhibited the growth up to 29.67 and 21.88 % respectively. Least inhibition was observed in T. atroviride. In respect of plant extract, minimum growth and higher inhibition was noted in ginger rhizome extract (63.10 mm) with 29.89% inhibition followed by 10.36% in neem.